Dynamic Characterization and Vibration Analysis of a Four-Story Mass Timber Building - Mugabo, Ignace; Barbosa, Andre R.; Riggio, Mariapaola (Frontiers in Built Environment, 2019)
Mass timber construction has been gaining momentum in multi-story residential and commercial construction sectors in North America. As taller mass timber buildings are being planned and constructed, in-situ dynamic tests of this type of construction can be performed to further validate their design and use. As part of this larger effort, an in-situ dynamic characterization testing campaign based on ambient vibration measurements was conducted on a recently constructed four-story mass timber building located in Portland, Oregon. The building features cross-laminated timber (CLT) floors, a glued laminated timber (GLT) framing gravity system, and light-frame shear walls and steel HSS hold-downs that compose the lateral resisting system of the building. Ambient vibration acceleration testing data were collected using 18 accelerometers that were wired to a portable data acquisition system in two experimental setups. Approximately two hours of bi-directional horizontal acceleration data were recorded. In this paper, two operational modal analysis methods are used for estimating the modal parameters (frequency, damping, and mode shapes) based on the data collected. In addition, a multi-stage linear Finite Element (FE) model updating procedure is presented for this building type and the FE estimates of frequencies and mode shapes are compared to estimates from the collected data. The calibrated FE model provides confidence to the operational modal results, and presents a comprehensive modal characterization of the building. At ambient levels of excitation, the developed FE model suggests that stiffness of the non-structural elements, such as the exterior wall cladding and glazing affects the modal response of the building considerably. Lessons learnt on this unique and first of a kind four-story structure constructed in the United States and implications for taller mass timber buildings are summarized and provide valuable insight for the design and assessment for this building type under future dynamic excitation events.